Literature Review the Relationship of Family Environment with Smoking Behavior in Adolescents - Ghozali Ghozali; Hanifah Tanjung; Rusni Masnina (Institute of Computer Science (IOCS), 2022)
Smoking behavior or tobacco use among adolescents has become a very serious global health problem. The family environment is the first environment for adolescents that has a major impact on their behavior, including smoking behavior. The purpose of this study was to determine the relationship between family environment and smoking behavior in adolescents. The method used in this study was Literature Review. The data used in this study were sourced from the publication database of Taylor & Francis, PubMed, Google Scholar and Science Direct with the keywords cigarette, smoking behavior, family environment, and adolescent. Family environment had a significant effect on smoking behavior in adolescents. Some of the related factors were the provision of pocket money for children and adolescents, family parenting, parental communication, harmony in the household, parental income, family members who smoke and inculcating the norms and spiritual values taught by parents in order to equip a child not to smoke. Recommendations: There was a significant relationship between family environment and smoking behavior in adolescents. Greater attention to the family environment of children and adolescents is needed in the context of early prevention of smoking behavior in adolescents.